Use of faith-based social service providers in a representative sample of urban homeless women - Heslin, Kevin C. (Springer-Verlag, 2003)
There are few quantitative studies on the characteristics of homeless persons who use faith-based social service providers. To help address the lack of information in this area, we analyzed survey data on 974 participants in the University of California at Los Angeles (UCLA) Homeless Women’s Health Study, a representative sample of homeless women at shelters and meal programs in Los Angeles County. The primary objective of this analysis was to estimate the association of religious affiliation, race/ethnicity, income, and other client characteristics with the use of faith-based programs. In interviews at 78 homeless shelters and meal programs, study respondents provided information about their religious affiliation and other social and demographic characteristics. The names of the organizations were examined, and those with names that referenced specific religions or contained words connoting religiosity were designated as “faith based”. At the time they were selected for study participation, 52% of respondents were using the services of faith-based providers. In multivariate logistic regression analysis, lower odds of using these providers were estimated for participants with no religious affiliation (compared with Christian respondents) and for African Americans and Latinas (compared with whites). There is evidence of systematic differences between the clients of faith-based and secular social service providers. The benefits of increased funding through a federal faith-based policy initiative may accure primarily to subgroups of clients already using faith-based programs.